1993
DOI: 10.1037/h0079398
|View full text |Cite
|
Sign up to set email alerts
|

Mothers of sexually abused children: Trauma and repair in longitudinal perspective.

Abstract: Mothers whose children had been sexually abused reported experiencing serious psychological symptoms following disclosure of the abuse. Over a one-year period, their emotional status improved. Strong relationships between mothers' reports of their own and their children's symptoms were accompanied by persistent discrepancies between maternal and direct assessments of the children's emotional states. Findings suggest that addressing maternal distress is important to the study and treatment of child sexual abuse. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
9

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 44 publications
2
42
0
9
Order By: Relevance
“…4,5 Cinsel istismara uğramış çocukların anne-babaları kontrol grubunun anne-babalarına göre daha fazla TSSB tanısı almıştır. 6,7 Başka bir çalışmada Cİ'ye uğramış çocukların annelerinin %15,6'sının şimdiki TSSB kriterlerini, %36,7'sinin yaşam boyu TSSB kriterlerini karşıladığı bulunmuştur. Ayrıca bu çalışmada, TSSB'li annelerin çocuklarının TSSB'si olmayan annelerin çocuklarına göre daha fazla TSSB semptomları sergiledikleri gösterilmiştir.…”
Section: Introductionunclassified
“…4,5 Cinsel istismara uğramış çocukların anne-babaları kontrol grubunun anne-babalarına göre daha fazla TSSB tanısı almıştır. 6,7 Başka bir çalışmada Cİ'ye uğramış çocukların annelerinin %15,6'sının şimdiki TSSB kriterlerini, %36,7'sinin yaşam boyu TSSB kriterlerini karşıladığı bulunmuştur. Ayrıca bu çalışmada, TSSB'li annelerin çocuklarının TSSB'si olmayan annelerin çocuklarına göre daha fazla TSSB semptomları sergiledikleri gösterilmiştir.…”
Section: Introductionunclassified
“…Rather, the majority of nonoffending caregivers appear to suffer greatly or be traumatized upon discovery of their children's sexual abuse (Corcoran, 1998;Deblinger et al, 1993;Manion et al, 1996;Newberger, Gremy, Waternaux, & Newberger, 1993). Initial reactions by non-offending caregivers may include anger toward the perpetrator, displaced anger toward family members, guilt, self-blame, helplessness, panic, denial, shock, embarrassment, feelings of betrayal, a desire for secrecy, and fear for the child victim(e.g., Elliott & Carnes, 2001;Manion et al, 1996).…”
Section: Varied Impacts On Child Victims and Familiesmentioning
confidence: 99%
“…Initial reactions by non-offending caregivers may include anger toward the perpetrator, displaced anger toward family members, guilt, self-blame, helplessness, panic, denial, shock, embarrassment, feelings of betrayal, a desire for secrecy, and fear for the child victim(e.g., Elliott & Carnes, 2001;Manion et al, 1996). In a longitudinal study of maternal adjustment, Newberger et al (1993) found that non-offending mothers exhibited a range of symptoms, including: depression, anxiety, hostility, somatic symptoms, paranoid ideation, and psychoticism. In addition, non-offending caregivers may attempt suicide or require hospitalization following their child's disclosure (Deblinger et al, 1993), and often display symptoms of PTSD and grief symptomatology (Manion et al, 1996).…”
Section: Varied Impacts On Child Victims and Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compte tenu du rôle crucial qu'elles sont appelées à jouer auprès de l'enfant, il est étonnant que peu d'études empiriques aient porté spécifiquement sur les caractéristiques de ces mères. Les études effectuées mettent en lumière l'état de crise provoqué par le dévoilement de l'agression (Davies, 1995 ;Deblinger et al, 1993 ;Hiebert-Murphy, 1998 ;Manion et al, 1996 ;Newberger et al, 1993). Cette situation de crise est susceptible d'éprouver les capacités adaptatives de la mère, d'autant plus que le dévoilement de l'agression peut ne pas être la seule situation difficile avec laquelle elle doive composer.…”
unclassified